EFEKTIVITAS KOMBINASI PURSED LIP BREATHING DAN DISTRACTIVE AUDITORY STIMULI TERHADAP NILAI PEAK EKSPIRATORY FLOW PADA PASIEN PPOK DI RSUD JOMBANG - Rozi, Fahrur (LPPM STIKes Bahrul Ulum Jombang, 2019)
Dyspnea is a condition that describes the sensation of shortness of breath, which is characterized by airflow obstruction, or difficulty breathing and shortness of breath are often associated with heart or respiratory disease, This study aims to determine the effectiveness of the combination pursed Lip Breathing and Distractive Auditory Stimuli to perception of Dyspnea and Peak expiratory Flow Rate in COPD patients. This study design used queasy Experiment one group pretest-posttest with a control group, studies were conducted in 32 patients with COPD in the Pavilion Cempaka Jombang General Hospital in February-March 2018. Respondents were divided into 4 groups aged between 50-79 years. Group 1 was given therapy Breathing Lips pursed, Distractive Auditory Stimuli group 2, group 3 combination Breathing Lips pursed and Distractive Auditory Stimuli, group 4 as the control group. Results and Analysis: Analysis of paired t-test PLB had a significant value of p = 0.000 (p <0.05), the DAS had a significant value of p = 0.000 (p <0.05), the combination had a significant value of p = 0.000 (p <0.05 ). While statistically MANOVA test the combination group as evidenced by the value of Wilks' Lambda indicated the significance level of 0.000 (p <0.05). This shows the differences between the mean value of Dyspnea and PEF in the treatment group and the control group with the power difference of 0.648 in the combination group. Discussion and Conclusion: Nurses can use the PLB and DAS combination therapy as an alternative therapy for reducing the perception of dyspnea and increase the value of PEF in patients with COPD.